ANALYSIS OF NATURALISM PAINTING IN BASUKI ABDULLAH’S WORKS USING FERDINAND DE SAUSSURE’S SEMIOTIC THEORY - Nurlaila, Nikmah (Arty: Jurnal Seni Rupa, 2025)
Basuki Abdullah is a maestro painter from Indonesia who is a naturalist and realist. His work represents elements of natural and cultural beauty that are presented beautifully. This research aims to analyze the concepts or ideas and meanings contained in the work, including the color elements chosen so that they can form a portrait of the beauty of natural paintings. This research uses a qualitative method with Ferdinand de Saussure's semiotic theory approach which focuses on a sign and the related relationship between the signifier and the signified to reveal the hidden messages in the work. The results of the analysis show that Basuki Abdullah's works are able to bring out aesthetic values ​​in the landscape of natural beauty in Indonesia. This research provides further insight into the presentation of naturalist works of art by incorporating local elements into fine art elements while still highlighting their aesthetic value.